(untitled) (Global Journal of Management and Business Research, 2014)
The purpose of the article is to review the International Financial Reporting Standards (IFRS) convergence and its effect toward organizational change initiatives. It is expected that IFRS will replace U.S. GAAP in the near future. Most importantly, in 2010, the Securities and Exchange endorsed the convergence of IFRS and also urged firms to switch from the existing U.S. GAAP guidelines to the IFRS. Additionally, the Big 4 CPA firms have also endorsed the implementation of IFRS. Most interesting, the American Institute of Certified Public Accountants (AICPA) has suggested that IFRS would be included in all Certified Public Accounting (CPA) exams starting in January 2011. From an educational perspective, this article will review U.S. universities/colleges accounting curriculums for student academic preparedness. At the end, recommendations will be offered to streamline IFRS throughout organizational and educational spectrums.